Protein crystals IR laser ablated from aqueous solution at high speed retain their diffractive properties: applications in high‐speed serial crystallography. Issue 6 (20th November 2017) - Schulz, Eike C.; Kaub, Johannes; Busse, Frederik; Mehrabi, Pedram; Müller-Werkmeister, Henrike M.; Pai, Emil F.; Robertson, Wesley D.; Miller, R. J. Dwayne
Abstract : This paper describes a proof‐of‐principle study demonstrating that protein crystals ablated by a picosecond infrared laser retain their diffractive properties. The crystals were ejected at high speed from an aqueous solution, collected and then used for structure determination by serial synchrotron crystallography. Abstract : In order to utilize the high repetition rates now available at X‐ray free‐electron laser sources for serial crystallography, methods must be developed to softly deliver large numbers of individual microcrystals at high repetition rates and high speeds. Picosecond infrared laser (PIRL) pulses, operating under desorption by impulsive vibrational excitation (DIVE) conditions, selectively excite the OH vibrational stretch of water to directly propel the excited volume at high speed with minimized heating effects, nucleation formation or cavitation‐induced shock waves, leaving the analytes intact and undamaged. The soft nature and laser‐based sampling flexibility provided by the technique make the PIRL system an interesting crystal delivery approach for serial crystallography. This paper demonstrates that protein crystals extracted directly from aqueous buffer solution via PIRL‐DIVE ablation retain their diffractive properties and can be usefully exploited for structure determination at synchrotron sources. The remaining steps to implement the technology for high‐speed serial femtosecond crystallography, such as single‐crystal localization, high‐speed sampling and synchronization, are described. This proof‐of‐principle experiment demonstrates the viability of a new laser‐based high‐speed crystal delivery system without the need for liquid‐jet injectors or fixed‐target mounting solutions.